The effect of tadabbur Al quran among undergraduate students at International Islamic University Malaysia - Ismail, Nurussyifa’; Ismail, Halim; Juhdi, Nurita; Ibrahim, Hasniza; Nik Abdullah, Nik Md. Saiful Azizi (Academic Inspired Network, 2023)
This research examines the effect of the tadabbur Al Quran among undergraduate students at International Islamic University Malaysia. A sample of 170 respondents was drawn through simple random sampling. This study was conducted using a quantitative method with analysis using IBM Statistical Package for the Social Sciences Statistics 27 software. A sample of 170 respondents was drawn through simple random sampling. Data were collected with a 38-item questionnaire whose reliability indexes ranged from 0.783 to 0.952 for the dimensions. Findings found that students are aware of the importance of tadabbur the Qur'an. In addition, students try to understand the verses of the Qur'an. So, this proves that implementing tadabbur the Qur'an can have a positive effect on undergraduate students at International Islamic University Malaysia